Estudio para el análisis y optimización de la red de agua potable de Sumak Yaku en el Cantón Otavalo Barrio Araque - Antamba Pulla, Alex Santiago (2017)
The present work considers the study for the analysis and optimization of the drinking water network of Sumak Yaku within which chapter 1 speaks generally about the Sumak Yaku administrative board, its background, geographical location, importance and characteristics. Chapter 2 mainly studies the pumping system, specifies zone 1 (catchment), zone 2 (tank and discharge), which reaches to the "TWINS" tanks, from which water is distributed to the communities. Chapter 3 indicates the technical specifications of the pipelines (lengths and diameters), motor-pump (power, flow and frequency), valves (types), slope and deposits. In addition the analysis of the total energy consumption in the pumping system (zone 1 and zone 2). Chapter 4 covers the analysis of the results of the current pumping system using Epanet 2.0 software, specifies tables of pressures, flow rates and roughness of the pipes used in their different zones. Later it indicates the technologies to improve and optimize the pumping system as it is a soft starter and the selection of a new pump with their respective characteristic curves and technical specifications. Finally, as technical annexes, it is possible to visualize the pumping system in a better way, as well as the technical specifications of the pump and the soft starter to be used obtained from their respective catalogs.